Modelling carbon isotopes of carbonates in cave drip water - Fohlmeister, Jens; Scholz, Denis; Kromer, Bernd; Mangini, Augusto (Geochimica et cosmochimica acta, 2011)
C isotopes in cave drip water are affected by both the C isotope composition of soil air and host rock carbonate. Furthermore, the C isotope composition of cave drip water strongly depends on the calcite dissolution system, i.e., open, closed and intermediate conditions. Here, we present a calcite dissolution model, which calculates the 14C activity and δ13C value of the dissolved inorganic carbon of the drip water. The model is based on the chemical equations describing calcite dissolution (H2O+CaCO3+CO2⇔Ca22HCO3-). The most important improvement, relative to previous models, is the combination of the open and closed system conditions in order to simulate the C isotope composition during intermediate states of calcite dissolution and the application to carbon isotope measurements on cave drip waters from Grotta di Ernesto, Italy. The major changes in the C isotope composition of the drip water occur in response to variations in the open-closed system ratio. Additionally, the 14C activity and the δ13C value of the drip water depend on changes in the partial pressure of soil CO2. Radiocarbon and δ13C values of the Grotta di Ernesto drip water are well reproduced by the model.
Gesehen am 26.01.2023